Hubungan Antara Pengetahuan dan Status Gizi Ibu Hamil dengan Kejadian Pre Eklamsia pada Ibu Hamil - Precelia Fransiska (Ilmiah Institut Citra Internasional, 2020)
Pre eclamsia every pregnant women Indonesia is prone to hypertension,wich is caused for 48 hours,during preganancy. The purpose this study was to determine is relationship between knowledge, and nutritional status the pregnant women with the incidence of pre-eclampsia, The women pregnant in Prabumulih Country Health Center in 2019. This study uses analytical survey using the cross sectional approach. The population of this were pregnant women who had preeclampsia at Prabumulih country, Health Center. This method take with by doing a test on pregnant women,from the results of research and analysis univariately, from 58 people with detail,36 (62,1%) people with good knowledge, and 20 (34,5%) people not good. From the results above to 29 (50%) people well also nutrished are, and 29 people nutrition have poor. Bivariate analysis showed that Knowledge had a significant relationship with pre-eclampsia (p value 0.006) and Nutritional Status had a significant relationship with the incidence of pre-eclampsia (p value 0.006). The conclusion of this study is that there is a relationship between knowledge and nutritional status of pregnant women with the incidence of pre-eclampsia in pregnant women in the Prabumulih Coutry Health Center 2019.